Does Multiple Leadership Styles Mediated By Job Satisfaction Influence Better Business Performance? Perception Of MNC Employees In Malaysia - Kader Ali, Noor Nasir; Tang, Song Yee (EDP Sciences, 2016)

(untitled)
One of the biggest challenges facing leaders today is the need to develop new business models that stress on effective leadership styles, employee job satisfaction and sustainability without sacrificing the financial and non-financial performance. The objective of this study is to examine the relationship between leadership styles and business performance of multinational companies operating in Malaysia mediated by job satisfaction. A quantitative study, using self-administered structured questionnaire, are issued using purposive sampling via direct distribution to 150 employees working in MNC. Analysis using Statistical Package for the Social Sciences (SPSS) and Partial Least Square (PLS) indicated that spiritual leadership style has the highest significant influence on job satisfaction, followed by authentic leadership style, transformational leadership style, and transactional leadership style. In addition, job satisfaction has a mediating effect on the relationship between each of the leadership styles, namely, transactional, transformational, authentic, and spiritual on business performance.